(untitled) (Global Journal of Management and Business Research, 2014)
Land surface shortwave albedo plays a central role in global and regional climate modeling. Remote sensing of surface properties and estimation of clear sky and surface albedo generally assumes that the albedo depends only on the solar zenith angle, which is verified as surface albedo decreases with increase of solar elevation angle (SAE), when SAE is greater than (value of angle=45deg.) it becomes constant. Fluctuations of soil moisture result in large variation in outgoing energy fluxes, and thus significant variation in near surface relative humidity and temperature. In this study analysis of radiation and other weather data collected from January 2009 to December 2009 at Ranchi in Jharkhand (85 30’E, 23 45’N,elev 652.272) are used to examines the diurnal and seasonal soil moisture variations with surface albedo and their relationship with soil moisture. The diurnal and seasonal soil moisture’s effect from rainfall is also discussed. From the analysis of monthly data indicate that surface albedo has inverse relation with soil moisture content. surface albedo, solar elevation angle, soil moisture.